Short Communication: Using ecological parameters to assess the sustainability of mangrove ecotourism in Jeneponto, South Sulawesi, Indonesia - HARDIANTY ASKAR; HAMZAH TAHANG; SUTINAH SUTINAH; SITTI FAKHRIYYAH; AHMAD BAHAR; JOEHARNANI TRESNATI; Ambo Tuwo (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Askar H, Tahang H, Sutinah S, Fakhriyyah S, Bahar A, Tresnati J, Tuwo A. 2021. Short Communication: Using ecological parameters to assess the sustainability of mangrove ecotourism in Jeneponto, South Sulawesi, Indonesia. Biodiversitas 22: 3571-3577. Mangrove forest is an essential ecosystem that provides various ecosystem services. Among various land use management in mangrove areas, ecotourism is considered as a sustainable economic activity that can improve socio-economic benefits while conserving the mangrove ecosystem. Therefore, ecotourism management must refer to sustainable development principles. This study aims to assess the sustainability status of mangrove forests in Idaman Mangrove Ecotourism in Balang Baru Village, Tarowang Sub-district, Jeneponto District, South Sulawesi, Indonesia using some parameters including the extent, density and diversity of mangrove vegetation, tidal height and animal biota that occurred in the mangroves. The study used line transect method and quadrat transect, and the data were analyzed using Rapfish (Rapid Appraisal for Fisheries) method. The study indicated that the sustainability status of IME for the ecological dimension was in the entirely sustainable category with an ecological dimension value was 58.50. While the mangrove is currently managed sustainably, to go further, it requires all stakeholders' cooperation in improving the dimensions of sustainability, which had a low value, especially the mangrove trees thickness.